Functional Carbons Remedy the Shuttling of Polysulfides in Lithium–Sulfur Batteries: Confining, Trapping, Blocking, and Breaking up. (25th March 2018) - Shi, Huifa; Lv, Wei; Zhang, Chen; Wang, Da‐Wei; Ling, Guowei; He, Yanbing; Kang, Feiyu; Yang, Quan‐Hong
Abstract: Carbon materials are usually used as the sulfur host in rechargeable lithium–sulfur (Li–S) batteries that are considered as promising electrochemical energy storage systems. However, the "shuttling" caused by the soluble lithium polysulfides (LiPSs) formed by the reaction of Li and sulfur causes rapid capacity fade and low sulfur utilization, greatly hindering their practical use. The carbon materials can also be tailored to prevent LiPS shuttling because of their abundant porosity and controllable surface chemical properties, which are divided into four specific functions: confining, trapping, blocking, and breaking up. Confinement means physically confining the LiPSs in pores in the carbon while trapping refers to chemical adsorption on the carbon surface to restrict their diffusion and promote their transformation to insoluble Li2 S2 /Li2 S. Blocking means placing a barrier in the cells to inhibit LiPS diffusion to the anode, while breaking up means decreasing the size of the sulfur moiety to increase its affinity with carbons. The advantages and disadvantages of functional carbons in relation to these four functions are summarized and the specific ways to achieve them are highlighted. The design of advanced carbons with synergistic functions is discussed and some perspectives on the future development of carbons in Li–S batteries are given. Abstract : Functional carbon materials are widely used in lithium–sulfur batteries to remedy the shuttling of lithium polysulfides, which can be generalized into four different functions: confining, trapping, blocking, and breaking up. Research advances for the design of carbons with different roles and the corresponding performance improvement are discussed in detail. The perspectives on the challenges and solutions for future applications are proposed.